Exploring the Experiences of Individuals Diagnosed with Metastatic Non-Small-Cell Lung Cancer: A Qualitative Study. - Scruton, Sarah; Hovey, Caroline; Kendell, Cynthia; Urquhart, Robin (Current Oncology, 2025)
Simple Summary: Improvements in cancer treatments have led people with metastatic non-small-cell lung cancer (mNSCLC) to live much longer than before. However, most existing support services are designed for patients diagnosed at an earlier stage who were treated with the goal of curing their cancer, and do not fully meet the needs of those living long term with metastatic cancer. In this study, eight Canadians with mNSCLC shared their experiences. While generally satisfied with their medical care, they experienced little support for side effects, emotional challenges, and practical challenges (i.e., financial burdens). Existing supportive care programs (i.e., exercise programs) were appreciated but often provided as short-term services, were difficult to access, and required patients to find them on their own. This study shows the need for supports tailored to those with mNSCLC, better healthcare coordination, and expanded resources. These findings can guide future research and the development or adaptation of resources to help address these challenges. Advancements in targeted therapies and immunotherapies have improved survival for individuals with metastatic non-small-cell lung cancer (mNSCLC), creating a growing population of Canadians living long-term with the disease. These individuals face ongoing physical, emotional, and practical challenges, yet existing supportive care services are often designed for patients receiving curative intent treatment and may not adequately address the challenges of those undergoing continuous treatment. To explore these experiences and inform the development of supports tailored to their needs, eight participants with mNSCLC completed one-on-one virtual interviews. They described limited support for managing side effects and psychosocial concerns despite general satisfaction with oncology care. Fatigue and cognitive challenges impacted daily functioning, and emotional challenges (e.g., fear of progression, stigma, and difficulty finding meaning) impacted quality of life. Financial burden, including unexpected costs and loss of income, further affected their well-being. Existing supports, such as exercise programs, were viewed positively but were often difficult to access, were offered only short-term, and required patients to find them independently. Recommendations included improved coordination and communication across the healthcare system, alongside tailored interventions such as navigation services, resource directories, health promotion supports, and expanded peer support. Overall, people living long term with mNSCLC face distinct challenges and unmet supportive care needs, highlighting the importance of integrating supportive services into routine oncology care.